What Detoxifies Shame in Integrative Psychotherapy? an Interpretative Phenomenological Analysis - Anthony Friel, Joseph (British Journal of Psychotherapy, 2016)
This study investigated the detoxification process of shame in integrative psychotherapy from the client's perspective, focusing on the experience of shame and the interventions used in working with toxic shame. Through identifying the detoxification process, successful therapeutic outcomes that reduced shame over time were determined with further exploration into the experience of the shame phenomenon. Interpretative phenomenological analysis was used to analyse data from transcripts of semi‐structured recorded interviews from a sample of trainee/qualified therapists who had experienced shame as clients. The findings from the study evidence the separating and isolating qualities of the shame experience, an experience that was crippling and correlated with development and early infantile relationships. The findings of this study highlight how shame is experienced and the fundamental role therapists have in detoxifying shame through recognizing, understanding and working to normalize it. Sensitivity to the shame experience is crucial so as not to compound the shame experience further. The need to be sensitive to regression in treatment, the need for a secure attachment within a relational oriented psychotherapy such as integrative psychotherapy and the centrality of the relationship in the reparative process are seen as fundamental to the effective management of toxic shame. In view of integrative psychotherapy being influenced by a variety of psychoanalytical theories, this paper draws upon psychoanalytic and humanistic perspectives in the analysis and interpretation of the findings.